Paroxysmal supraventricular tachycardias: modern principles of diagnostics and treatment - A. V. Vetluzhsky; I. G. Fomina (Кардиоваскулярная терапия и профилактика, 2005)
The article is devoted to one of the most actual problems in modern arrhythmology - treatment of paroxysmal supraventricular tachycardias. Modern views on diagnostics and treatment of atrio-ventricular (AV) nodal reciprocating tachycardia and AV reciprocating tachycardia with extra nodal accessory pathways’ involvement are presented. Vagal maneuvers for paroxysm termination are described in detail. Algorithms for differential diagnostics and antiarrhythmic therapy selection, according to arrhythmic mechanisms, are presented.